Nootropic and Adaptogenic Effect of Combined Use of Cortexin with Polyunsaturated Fatty Acids Concentrate under Experimental Dislipidemia - Tatyana I. Sangadieva (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
Background. We studied the effect of combined application of omega-3 polyunsaturated fatty acid concentrate, based on seals fat, with parenteral administration of brain cortex polypeptide preparation on cognitive-research reactions and adaptation of rats under experimental hyperlipidemia. The composition of the myelin sheaths of neurons is represented by a protein-lipid complex, which is a part of the cell membrane, the imbalance of which leads to a number of neurological diseases.The aim of the study was to confirm experimentally that the combined use of drugs, based on essential polyunsaturated fatty acids and polypeptides, would influence more effectively on neurometabolic processes in neurons, compared to their application separately.Materials and methods. Wistar rats were used. They were on a special atherogenic diet to build the model of hypercholesterolemia. The pharmacological effects of drugs were evaluated in the Open Field and Morris Water Maze tests.Results. The study found that in rats, who received a combination of polyunsaturated fatty acids concentrate with Cortexin injections, and undergoing atherogenic diet, the overall motor activity increased significantly in the Open field test, at the same time the number of acts of defecation and grooming decreased. The Morris Water Maze test results indicated an increase in the level of spatial memory and orientation, which shows a high level of adaptability and adaptation to new conditions, a decrease in the level of anxiety.Conclusions. The results demonstrated a more pronounced and prolonged nootropic and adaptogenic action of the complex use in comparison with the use of the studied agents as monotherapy.